Estudo da adequação do profissional bibliotecário para atuação nas bibliotecas do Serviço Social do Comércio - Administração Regional no estado do Rio de Janeiro - SESC/ARRJ - Lima, Nancy André de (1988)
Investigation of the factors which influenced and led to the resignation of librarians from the library of the Social Service for Commerce, Regional Agency in Rio de Janeiro (SESC/ARRJ) in the last six years. An extensive review of the literature in the areas of library education and library market in Brazil provided the conceptual framework for the study. Several authors pointed out that the basic curriculum for the education of librarians in the country, established in 1962, was outdated and did not correspond any more to the needs of the market. They also identified many factors which can affect the librarians' market such as salary, local of work, lack of human resources in library, working hours, etc. The investigation was carried out through the application of questionnaires, raising questions to the librarians such as library education, experience, kind and time of work at SESC/ARRJ, activities, problems, barriers, expectations and perceptions about his/her work. Interviews were made with professionals of others areas who worked with the librarians in the provision of cultural and leisure activities offered by the Institution; they were asked about their views on the library and the librarians' performance. A correlation was made among the findings of the study with the views expressed in the review of the literature to corroborate the author's opinions and/or the findings of earlier studies. A profile of the librarians who resigned their positions at the SESC/ARRJ was pointing out to characteristics, which did not differentiate them much from those who stayed in their positions. The final conclusion of the study was that, more than the factors raised in the literature, personal characteristics and needs led to the abandonment or maintenance of the librarians at the Institution.